2020
DOI: 10.1155/2020/5892924
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Anisotropy and Scale Effects on the Strength Characteristics of Defected Rockmass

Abstract: Discontinuous defect in the rockmass is a key influential factor in controlling the strength behavior, and how to estimate the anisotropic strength and scale effect on the defected rockmass is the remaining challenging focus in engineering application. In the present study, intact tuff samples cored from the Xiabeishan tunnel engineering in situ are conducted by experiment tests (i.e., uniaxial compression test, triaxial compression test, and Brazilian tensile test) to obtain the corresponding mechanical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…It was found that the joint spacing predominantly controlled the extent of deformation above the excavation. Liu et al (2020) investigated the anisotropy and scale effects on the strength characteristics of the defected rock mass using a synthetic rock mass (SRM) method, which was coupled with the discrete element method (DEM) and discrete fracture network (DFN). The test results showed that defects in the rock mass played a vital role in failure mode and strength behavior.…”
Section: Causes Of Scale-dependent Behaviormentioning
confidence: 99%
“…It was found that the joint spacing predominantly controlled the extent of deformation above the excavation. Liu et al (2020) investigated the anisotropy and scale effects on the strength characteristics of the defected rock mass using a synthetic rock mass (SRM) method, which was coupled with the discrete element method (DEM) and discrete fracture network (DFN). The test results showed that defects in the rock mass played a vital role in failure mode and strength behavior.…”
Section: Causes Of Scale-dependent Behaviormentioning
confidence: 99%
“…It was found that the joint spacing predominantly controlled the extent of deformation above the excavation. Liu et al [28] investigated the anisotropy and scale effects on the strength characteristics of the defected rock mass using a synthetic rock mass (SRM) method, which was coupled with the discrete element method (DEM) and discrete fracture network (DFN). The test results showed that defects in the rock mass played a vital role in failure mode and strength behavior.…”
Section: Causes Of Scale-dependent Behaviormentioning
confidence: 99%
“…Ying et al [16] established a method based on volume rupture strength (P32) and a statistical test method to estimate rock mass REV. Wu et al [17] studied the effect of size on bulk modulus, while taking into account the effect of the model location, and reported that the REV size was 18 m. Liu et al [18] elucidated the size effect of the defective rock mass strength through uniaxial and confining pressure tests and obtained a REV size of 5 m × 10 m. Hu et al [19] obtained the relationship between the characteristic size of the rock elastic modulus and the PJS. Overall, although the bulk modulus has been extensively studied, only a few researchers investigated the relationship between the characteristic size of the bulk modulus (CSBM) and PJS and established a model of the CSBM and PJS.…”
Section: Introductionmentioning
confidence: 99%